Youth Participation in Village Development Through Karang Taruna: Partisipasi Pemuda dalam Pembangunan Desa Melalui Karang Taruna - Agustina, Isna Fitria; Dandi, Stevanus (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Youth engagement is essential in promoting inclusive and sustainable village development. Specific Background: Karang Taruna, as a youth organization, plays a pivotal role in mobilizing community initiatives, yet participation levels often remain low. Knowledge Gap: Limited studies examine youth involvement in development from the perspective of social empowerment and institutional support at the village level. Aims: This study analyzes the forms, challenges, and contributions of Karang Taruna in developing Kemiri Village, Sidoarjo Regency. Results: The findings reveal that youth participation is mostly limited to labor and material assistance, with minimal involvement in decision-making or innovation. However, initiatives such as catfish cultivation programs and community cleanliness efforts indicate emerging awareness among youth. Novelty: The study introduces a typology of youth participation (thought, skill, labor, and property) to assess community development engagement. Implications: Strengthening leadership training, community partnerships, and local government collaboration can enhance sustainable youth contribution to village progress. Highlights: Karang Taruna contributes to local empowerment. Youth involvement remains limited in decision-making. Leadership training fosters social participation.